Epidemiology, Etiology, and Treatment of Isolated Cleft Palate - Burg, Madeleine L.; Chai, Yang; Yao, Caroline A.; Magee, William; Figueiredo, Jane C. (Frontiers in Physiology, 2016)
Isolated cleft palate (CPO) is the rarest form of oral clefting. The incidence of CPO varies substantially by geography from 1.3 to 25.3 per 10,000 live births, with the highest rates in British Columbia, Canada and the lowest rates in Nigeria, Africa. Stratified by ethnicity/race, the highest rates of CPO are observed in non-Hispanic Whites and the lowest in Africans; nevertheless, rates of CPO are consistently higher in females compared to males. Approximately fifty percent of cases born with cleft palate occur as part of a known genetic syndrome or with another malformation (e.g., congenital heart defects) and the other half occur as solitary defects, referred to often as non-syndromic clefts. The etiology of CPO is multifactorial involving genetic and environmental risk factors. Several animal models have yielded insight into the molecular pathways responsible for proper closure of the palate, including the BMP, TGF-β, and SHH signaling pathways. In terms of environmental exposures, only maternal tobacco smoke has been found to be strongly associated with CPO. Some studies have suggested that maternal glucocorticoid exposure may also be important. Clearly, there is a need for larger epidemiologic studies to further investigate both genetic and environmental risk factors and gene-environment interactions. In terms of treatment, there is a need for long-term comprehensive care including surgical, dental and speech pathology. Overall, five main themes emerge as critical in advancing research: (1) monitoring of the occurrence of CPO (capacity building); (2) detailed phenotyping of the severity (biology); (3) understanding of the genetic and environmental risk factors (primary prevention); (4) access to early detection and multidisciplinary treatment (clinical services); and (5) understanding predictors of recurrence and possible interventions among families with a child with CPO (secondary prevention).